If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -13 = 4x + -24 Reorder the terms: -13 + 3x = 4x + -24 Reorder the terms: -13 + 3x = -24 + 4x Solving -13 + 3x = -24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 3x + -4x = -24 + 4x + -4x Combine like terms: 3x + -4x = -1x -13 + -1x = -24 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + -1x = -24 + 0 -13 + -1x = -24 Add '13' to each side of the equation. -13 + 13 + -1x = -24 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = -24 + 13 -1x = -24 + 13 Combine like terms: -24 + 13 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| 4x+2[4-2(x+2)]=2x-1 | | 4(m-4)=12 | | 18.8=2(3.14)r | | 22=2l+2(7) | | Y=x^5-1x^3-6x | | 9y=-45x+45 | | -y^2+9y-9=0 | | 2x+10=20x-20 | | 5m*5m+27m+34=0 | | x=2y+2 | | 4y^2+16y+18=0 | | 3x+3=105 | | 6x+10=70-4x | | 2x=24-6x | | x-0.4=2x | | 6x-20=-14 | | 12=5+f | | 6x=90-3x | | 5x+7=9x+11 | | 10x+6=26 | | 8x-53=6x-5 | | 3x+7=27-2x | | 3z-9=4z-7 | | 51-2x=7x | | 2x=5-3x | | r+4.9=-5.4 | | 62-4x=5x+16 | | -2=12+x | | 18x=414 | | 11-9x=71-37x | | 3x=48-3x | | 8x+2x=9x+1 |